If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15x=69.6
We move all terms to the left:
15x-(69.6)=0
We add all the numbers together, and all the variables
15x-69.6=0
We move all terms containing x to the left, all other terms to the right
15x=69.6
x=69.6/15
x=4+2.6666666666667/4.1666666666667
| 7n^2+10=-19n | | 18+7r=18 | | -2x+1=3x-4 | | 4x-3-3(2x)=12+3x | | (2x+15)+6=180 | | 50=-8z-2z | | 50=-8z–2z | | 3(u+3)=15 | | u/5+8=38 | | 9x-14=25 | | f(-4)=3(-4)-2 | | 7t+4=102−7t | | 5(z-2)+3z=1 | | 2x+2=x+ | | 10x+5=5x+60 | | y=-25(0)+170 | | 2f+7f+9=0 | | 3x(2)+2x=360 | | 4(1+4x)= | | 4x+14=6x-10 | | x+9=-2x+24 | | -7w+5w+2+4=0 | | 70x+4x=1500 | | 2x+11=5x+23 | | 2(4x5)-3=5x(2+1) | | 3x-3=-3x+15 | | 3=5v-2 | | (x-(x-1)/5-2)/5+(x-(x-1)/5-(x-(x-1)/5-2)/5-6-(x-(x-1)/5-(x-(x-1)/5-2)/5-3)/5-(x-(x-1)/5-(x-(x-1)/5-2)/5-4-(x-(x-1)/5-(x-(x-1)/5-2)/5-3)/5)/5-(x-(x-1)/5-(x-(x-1)/5-2)/5-5-(x-(x-1)/5-(x-(x-1)/5-2)/5-3)/5-(x-(x-1)/5-(x-(x-1)/5-2)/5-4-(x-(x-1)/5-(x-(x-1)/5-2) | | (x-(x-1)/5-2)/5+(x-(x-1)/5-(x-(x-1)/5-2)/5-6-(x-(x-1)/5-(x-(x-1)/5-2)/5-3)/5-(x-(x-1)/5-(x-(x-1)/5-2)/5-4-(x-(x-1)/5-(x-(x-1)/5-2)/5-3)/5)/5-(x-(x-1)/5-(x-(x-1)/5-2)/5-5-(x-(x-1)/5-(x-(x-1)/5-2)/5-3)/5-(x-(x-1)/5-(x-(x-1)/5-2)/5-4-(x-(x-1)/5-(x-(x-1)/5-2) | | 4-2y+8y= | | 4x-3=-6x+4 | | -9x=-2−10x |